QUANTITATIVE ESTIMATION OF GINSENOSIDES IN DIFFERENT AGES OF PANAX VIETNAMENSIS AND THEIR ANTI-PROLIFERATION EFFECTS IN HELA CELLS - Vo, Hoang Tung; Ghimeray, Amal Kumar; Vu, Ngoc Thang; Jeong, Yeon-Ho (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The objective of study was to investigate the major compounds of ginsenosides in Panax vietnamensis in its growing stages and their anti-proliferative activity in HeLa cells.Materials and Methods: The roots with different ages were analyzed by HPLC/MS. Anti-proliferation activity of P. Vietnamensis ginseng in HeLa cells was investigated using MTT assay.Results: Three main compounds of ginsenoside, Rb1, Rg1 and majonoside R2 were increased with the increasing of age. However, ginsenoside Rc, Re, Rd and Rg3 did not show any alteration with growing age. The major compound majonoside R2 was accumulated maximum in 5 years old ginseng. According to the data, the anti-proliferation activity was directly proportional to the growing ages of ginseng. The eleven years old ginseng showed maximum effect than the younger roots. This effect may be related to the concentration of ginsenosides or majonoside R2 content in P. Vietnamensis.Conclusion: The concentration of ginsenoside content in the roots of P. Vietnamensis is directly related to the growing ages. Overall, due to the higher concentration of ginsenoside in mature ginseng root, Panax vietnamensis ginseng can be used as an effective anti-proliferative drug.